2020
DOI: 10.3390/su12052081
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Logit Models for Travelers’ Mode Shifting Considering Bike-Sharing

Abstract: This study quantifies the impact of individual attributes, the built environment, and travel characteristics on the use of bike-sharing and the willingness of shifting to bike-sharing-related travel modes (bike-sharing combined with other public transportation modes such as bus and subway) under different scenarios. The data are from an RP (Revealed Preference) survey and SP (Stated Preference) survey in Nanjing, China. Three mixed logit models are established: an individual attribute–travel characteristics mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…With regard to e-bike (including e-cargobike) sharing, it has been found that a range of recurring demographic factors, such as age, gender, income, and education, tend to be associated with bike sharing usage or intention [6,11,14,15,17,22]. For instance, in their review of shared e-mobility services, Liao and Correia [6] conclude that shared mobility users are mostly male, middle-aged, and tend to have higher levels of income and education (see also [23]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With regard to e-bike (including e-cargobike) sharing, it has been found that a range of recurring demographic factors, such as age, gender, income, and education, tend to be associated with bike sharing usage or intention [6,11,14,15,17,22]. For instance, in their review of shared e-mobility services, Liao and Correia [6] conclude that shared mobility users are mostly male, middle-aged, and tend to have higher levels of income and education (see also [23]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of Asian or developing countries, studies undertaken in China suggest that habitual personal vehicle users are less likely to shift to a potential new transit mode (12). Studies on bike-sharing identify younger, highly educated, and low-income travelers without a car as having a higher propensity to use bikesharing (15) These studies use a choice-based sampling strategy based on the primary mode choice, thus leading to potential selectivity bias. Another issue is the use of only a single target mode for shift and assuming independence between the original mode and the mode shift decision.…”
Section: Mode Shift and The Type Of Modes Shiftedmentioning
confidence: 99%
“…However, as the price of the private car became much cheaper, carsharing turned to be less attractive until the rising fuel prices and heavy road congestion have drawn the public's attention back to carsharing [8]. In recent years, shared mobility becomes a hot topic in transport development, and so does electrification [12,16,17]. Electric carsharing, a form of carsharing which rents EVs to people, combines these two items and is expected to inherit their positive impacts on sustainable transport development, including guiding the public to form a sustainable travel behavior [6], improving the accessibility and flexibility of the urban transport [12], reducing car ownership [5], vehicle kilometres of travel [9], traffic congestion [18], parking land use [18], and greenhouse gas emissions [11].…”
Section: Literature Reviewmentioning
confidence: 99%